Diet and Dyslipidemia in HIV Infected Pediatric Patients who Received Lopinavir/ritonavir (LPV/r) - มูลศาสตร์ วิศัลย์; กลิ่นมาลัย ลัดดาวัลย์; อัศวพิพิธ เจริญสุข; เจริญพักตร์ รัชนู; อัมพรอารีกุล สมถวิล; จิระคุณ นภา (Disease Control Journal, 2012)
This retrospective cohort study was design to evaluate whether tight diet control (intervention) can reduce dyslipidemia in HIV infected pediatric patients who received Lopinavir/ritonavir (LPV/r) from 1 Jan 2007 to 31 Dec 2010. There were 62 patients. Inclusion criteria were patient under 18 year old and LPV/r-base therapy. Lipids measurements was done before and after initial LPV/r therapy and another lipids measurements was done after intervention, collected from medical record. Mean cholesterol level before and after intervention were observed ( 200.19±49.03 vs 204.00±67.40 mg/dl, p = 0.615). Mean triglyceride level before and after intervention were observed (162.58±88.75 vs 150.05±71.23 mg/dl, p = 0.140). Mean cholesterol level before and after LPV/r-base therapy were observed (189.44±48.76 vs 200.19±49.03 mg/dl, p = 0.039). Mean triglyceride level before and after LPV/ r-base therapy were not difference ( p= 0.583). Conclusion tight diet control can reduce dyslipidemia in HIV infected pediatric patients who received LPV/r.